2015
DOI: 10.1104/pp.15.00570
|View full text |Cite
|
Sign up to set email alerts
|

SHORT VEGETATIVE PHASE Up-Regulates TEMPRANILLO2 Floral Repressor at Low Ambient Temperatures

Abstract: Plants integrate day length and ambient temperature to determine the optimal timing for developmental transitions. In Arabidopsis (Arabidopsis thaliana), the floral integrator FLOWERING LOCUS T (FT) and its closest homolog TWIN SISTER OF FT promote flowering in response to their activator CONSTANS under long-day inductive conditions. Low ambient temperature (16°C) delays flowering, even under inductive photoperiods, through repression of FT, revealing the importance of floral repressors acting at low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 39 publications
(91 reference statements)
2
23
0
Order By: Relevance
“…Together with the binding of TEMs to MIR172C chromatin, the effect of TEMs on MIR172A , MIR172B and MIR172C RNAs and mature miR172 levels (Figure ) indicates that TEMs regulate flowering partly through miR172, by repressing the expression of MIR172A , MIR172B and directly that of MIR172C . Taking into account previous reports, we can conclude that the regulation of flowering time by TEMs is mainly mediated by FT, TSF and GA (Castillejo and Pelaz, ; Osnato et al ., ; Marín‐González et al ., ), but also partially by miR172.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Together with the binding of TEMs to MIR172C chromatin, the effect of TEMs on MIR172A , MIR172B and MIR172C RNAs and mature miR172 levels (Figure ) indicates that TEMs regulate flowering partly through miR172, by repressing the expression of MIR172A , MIR172B and directly that of MIR172C . Taking into account previous reports, we can conclude that the regulation of flowering time by TEMs is mainly mediated by FT, TSF and GA (Castillejo and Pelaz, ; Osnato et al ., ; Marín‐González et al ., ), but also partially by miR172.…”
Section: Discussionmentioning
confidence: 89%
“…It has been described that TEM1 and TEM2 are transcriptional repressors that directly downregulate FT , TSF , GA3ox1 and GA3ox2 (Castillejo and Pelaz, ; Osnato et al ., ; Marín‐González et al ., ). We show here that TEMs downregulate miR172 levels through direct binding to at least one MIR172 gene, MIR172C , and transcriptional repression of MIR172A , MIR172B and MIR172C (Figure ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…information from diverse redundant pathways (Yant et al, 2010;Tao et al, 2012;Marín-González et al, 2015). Similarly to other transcription factor families, it has been suggested that RAV genes may control additional biological aspects during plant development (Matías-Hernández et al, 2014).…”
Section: Tem Negatively Affects Trichome Initiation In Arabidopsismentioning
confidence: 99%
“…For example, FT transcription is directly activated by CONSTANS (CO), CRYPTOCHROME-INTERACTING BASIC-HELIX-LOOP-HELIX1 (CIB1), WRKY71, PHYTOCHROME-INTERACTING FACTOR 4 (PIF4) and Morf-related Gene 2 (MRG2) (Kumar et al, 2012;Liu et al, 2008Liu et al, , 2013Tiwari et al, 2010;Xu et al, 2014;Yu et al, 2016). In addition, FT transcription is also directly repressed by TEMPRANILLO (TEM) 1 and 2, TARGET OF EAT (TOE) 1 and 2, SHORT VEGETATIVE PHASE (SVP), CYCLING DOF FACTOR1 (CDF1), EARLY-FLOWERING MYB PROTEIN (EFM), SCHLAFMUTZE (SMZ) and SCHNARCHZAPFEN (SNZ) (Marin-Gonzalez et al, 2015;Mathieu et al, 2009;Song et al, 2012;Yan et al, 2014;Zhang et al, 2015). Thus, transcriptional regulation of FT expression plays a crucial role in flowering time control in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%